Hieroglyph of Time : the Petrarchan Sestina. - Shapiro, Marianne (University of Minnesota Press, 1980)
Hieroglyph of Time was first published in 1981. ""A dance of the intellect among words, "" Ezra Pound called the sestina. A poetic form invented by a Provençal troubadour, Arnaut Daniel, the sestina was elaborated and refined by Petrarch and is used today exactly as it was created. In Hieroglyph of Time, the first critical study of the sestina, Marianne Shapiro analyzes poems by Daniel, Petrarch, Pontus de Tyard, Sannazaro, Sidney, Spenser, Auden, Pound, Merwin, and Ashbery and discusses sestinas composed in German and Portuguese. In so doing, she traces a strand that links modern to Medieval p.